Raloxifene/SBE-β-CD Inclusion Complexes Formulated into Nanoparticles with Chitosan to Overcome the Absorption Barrier for Bioavailability Enhancement - Zaihua Wang; Yan Li (MDPI AG, 2018)
Raloxifene (RXF) is a hormone-like medication used for treating postmenopausal osteoporosis and estrogen-dependent breast cancer, yet associated with bad low bioavailability due to poor solubility. This study was intended to develop cyclodextrin/chitosan nanoparticles (ccNPs) for oral delivery of RXF in order to enhance the oral bioavailability. RXF-loaded ccNPs (RXF-ccNPs) were prepared by cyclodextrin inclusion followed by complexation with chitosan. RXF-ccNPs were fully characterized by particle size, morphology and in vitro drug release. The oral delivery efficacy and transepithelial transport potential were evaluated by pharmacokinetics, in situ single-pass intestinal perfusion, cellular uptake and ex vivo imaging. The resulting RXF-ccNPs were around 165 nm in particle size with a narrow distribution. The oral bioavailability of RXF was enhanced by 2.6 folds through ccNPs compared to RXF suspensions in rats. It was shown that RXF-ccNPs could improve the intestinal permeability of RXF, increase the cellular uptake of RXF and facilitate its transport across the absorptive epithelia. The results indicate that our developed ccNPs based on sulfobutylether-β-cyclodextrin and oligochitosan are a promising vehicle to orally deliver poorly water-soluble drugs over and above RXF.